IPCs Prove to Be Game-Changer in Citrus Production - Rezazadeh, Amir (EDIS, 2023)
Citrus trees face an array of threats that can impact fruit development and overall tree health. Pests, including aphids, mites, and other insects, can damage fruit and transmit diseases. Extreme weather events, such as hailstorms or heavy rains, can cause physical harm, leading to blemishes and reduced market value. In addition, citrus growers have consistently faced persistent challenges in the form of bacterial diseases, including citrus canker and citrus greening. These diseases not only have a negative impact on the quality of fruits, but also create a potential risk to the long-term viability of citrus industry.